Noticing and grammatical accuracy in ESL learners’ writing - Mohammad Lotfie, Maskanah; Abdul Samad, Arshad (Indonesian Journal of English Language Teaching, 2007)
This paper presents an overview of an exploratory study on the role of noticing in improving written accuracy. The noticing hypothesis, as conceptualised by Schmidt (1990, 2001), focuses on the need to enhance learners’ awareness of target language items in order to convert input into intake and subsequently internalise input as part of interlanguage. This study also takes into account the comprehensible output hypothesis (Swain, 1985, 1998) that proposes that output can promote noticing as it encourages learners to become aware of the gap between their interlanguage and the target language usage. These concepts have been translated into three types of feedback techniques for written output and the techniques are Enhancement, Reformulation, and Sequential. All three techniques function as a means to enhance learners’ awareness of past time forms and are therefore form-focused in nature but avoid explicit explanations of those target forms. Results indicate that noticing is influenced by the types of learner responses to the techniques. The structural components of a target form may influence the success of its acquisition. Statistical results suggest that all three instructional techniques were equally successful in enhancing noticing and in increasing learners’ written accuracy.